2016
DOI: 10.3390/h5030058
|View full text |Cite
|
Sign up to set email alerts
|

The White Mountain Recreational Enterprise: Bio-Political Foundations for White Mountain Apache Natural Resource Control, 1945–1960

Abstract: Among American Indian nations, the White Mountain Apache Tribe has been at the forefront of a struggle to control natural resource management within reservation boundaries. In 1952, they developed the first comprehensive tribal natural resource management program, the White Mountain Recreational Enterprise (WMRE), which became a cornerstone for fighting legal battles over the tribe's right to manage cultural and natural resources on the reservation for the benefit of the tribal community rather than outside in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Although scholars have highlighted the need for ancestral or traditional knowledge to inform Indigenous policy on community health and the environment (Chino and DeBruyn 2006; Tsosie 2010), few studies have identified and employed specific methods to facilitate this process. While we recognize that many tribes may already draw upon ancestral teachings to guide their decisions as nations (see, e.g., Tomblin 2016), our study offers one possible avenue for connecting elder knowledge and governmental policy, specifically in the realm of tribal land conservation. Although the Cherokee Nation continues to implement profit-driven land management programs such as cattle grazing leases on tribal lands, the PhotoVoice video conveys elder perspectives on these activities, suggests alternatives, and seeks to influence decision-makers who may not otherwise think critically about such practices.…”
Section: Discussionmentioning
confidence: 99%
“…Although scholars have highlighted the need for ancestral or traditional knowledge to inform Indigenous policy on community health and the environment (Chino and DeBruyn 2006; Tsosie 2010), few studies have identified and employed specific methods to facilitate this process. While we recognize that many tribes may already draw upon ancestral teachings to guide their decisions as nations (see, e.g., Tomblin 2016), our study offers one possible avenue for connecting elder knowledge and governmental policy, specifically in the realm of tribal land conservation. Although the Cherokee Nation continues to implement profit-driven land management programs such as cattle grazing leases on tribal lands, the PhotoVoice video conveys elder perspectives on these activities, suggests alternatives, and seeks to influence decision-makers who may not otherwise think critically about such practices.…”
Section: Discussionmentioning
confidence: 99%